Cultural Landscape and Tourism on Historic Ranches of the Pantanal Wetlands of Brazil - Correia de Araújo, Ana Paula; de S.M. Bicalh, Ana Maria o (Journal for Geography, 2009)
The rise of eco-tourism and rural tourism as new complementary activities which add value to traditional stock-raising functions on historic ranches located in the Pantanal Wetlands of Central-West Brazil is analyzed.  Differently from other rural enterprises of the booming Central-West, which produce the majority of Brazilian export commodities, the specific environmental conditions of seasonal wetlands and perennial swamp of the Pantanal restrict the viable options for gaining access to global markets.  Consequently, after 1990 ranchers of the Pantanal have developed tourist activities based on the spectacular natural beauty of the wetlands as well as the distinct ranching culture.  The ranches have modernized with amenities to attract domestic and foreign tourists and tourism has assumed an importance source of their income.